Math, asked by maahira17, 1 year ago

Find the second term and nth term of an A.P. whose 6th term is 12 and 8th term is 22.

Answers

Answered by nikitasingh79
32

Answer:

The second term is - 8 & nth term is -18 + 5n .

Step-by-step explanation:

Given :  

a6 = 12 & a8 = 22

a6 = 12

a + (6 - 1)d = 12

[an = a + (n -1)d]

12 = a + 5d  

a + 5d  = 12 ……………(1)

 

a8 = 22

a + (8 - 1)d = 22

a + 7d = 22 ………..,..(2)

On Subtracting eq 1 from eq 2,

a + 7d - (a + 5d) = 22 - 12

a + 7d - a - 5d = 10

2d = 10

d = 10/2

d = 5 ……………..(3)

On putting  the value of d = 5  in equation 1

a + 5d  = 12

a + 5(5) = 12

a + 25 = 12

a = 12 -  25

a = -13 …………..(4)

 

2nd term :  

a2 = a + (2 - 1)d

a2 = a + d

a2 = -13 + 5

[From eq 3 & 4]

a2 = -8

 

nth term :  

an = a + (n -1)d

an = -13 + (n -1)5

[From eq 3 & 4]

an = - 13 + 5n - 5

an = - 13 - 5 + 5n

an = -18 + 5n

Hence, the second term is - 8 & nth term is -18 + 5n .

HOPE THIS ANSWER WILL HELP YOU...

 

Answered by CaptainBrainly
14

GIVEN :

Sixth term of an A.P = 12

a + 5d = 12 ------(1)

Eighth term of an A.P = 22

a + 7d = 22 ----(2)

Solve eq - (1) & (2) to find difference (d)

a + 5d = 12

a + 7d = 22

(-)

-----------------

-2d = -10

d = 10/2

d = 5

Difference = 5

Substitute d in eq - (1) to find first term (a)

a + 5d = 12

a + 5(5) = 12

a + 25 = 12

a = 12 - 25

a = -13

First term = -13

Second term :

= a + d

= -13 + 5

= -8

an = a + ( n - 1 )d

= -13 + ( n - 1) 5

= -13 + 5n - 5

= -18 + 5n

= 5n - 18

Therefore, nth term of A.P is 5n - 18 and second term of A.P is -8.

Similar questions